‘In Drag’: Performativity and Authenticity in Zadie Smith’s "NW" - Pérez Zapata, Beatriz (International Studies. Interdisciplinary Political and Cultural Journal, 2014)
Zadie Smith’s latest novel, NW, presents a multiverse in chich multiplicity is driven into homogeneization by the forces of those dominant discourses that attempt to suppress the category of the “Other.” This paper focuses on the development of the two female protagonists. Their opposing attitudes towards motherhood, together with their confrontation with their origins, bring to the fore the performativity found in the discourses of gender, sexuality, class, and race. Thus, this paper will explore authenticity and performativity in a contemporary context, where patriarchal and neocolonial discourses still apply.